Job Safety Analysis for Hazard Identification in Cement Industry Warehouse Operations - Arilfa, Novita; Iftadi, Irwan (Teknoin, 2026)
Occupational safety in warehouse environments remains a major challenge due to complex material-handling activities that involve both mechanical and ergonomic risks. This study aimed to identify and analyze potential hazards in the Procurement and Warehouse Department of PT XYZ using the Job Safety Analysis (JSA) method and to propose effective control measures based on the Hierarchy of Control. The research employed a descriptive observational approach, including field observations, interviews, and risk evaluation using the Likelihood × Severity Scoring system. The analysis identified thirteen potential hazards across seven job activities, with 43% categorized as high risk, 43% as medium, and 14% as low. The most Significant risks were identified in forklift operation and manual material handling, contributing to mechanical and musculoskeletal hazards. The study concludes that the JSA method effectively provides a structured framework for risk identification and prioritization. The implementation of engineering, administrative, and ergonomic controls is essential to enhance safety performance and support sustainable workplace health, in alignment with ISO 45001:2018 and SDG 3 – Good Health and Well-Being.